2010
DOI: 10.1146/annurev-arplant-042809-112152
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic as a Food Chain Contaminant: Mechanisms of Plant Uptake and Metabolism and Mitigation Strategies

Abstract: Arsenic (As) is an environmental and food chain contaminant. Excessive accumulation of As, particularly inorganic arsenic (As(i)), in rice (Oryza sativa) poses a potential health risk to populations with high rice consumption. Rice is efficient at As accumulation owing to flooded paddy cultivation that leads to arsenite mobilization, and the inadvertent yet efficient uptake of arsenite through the silicon transport pathway. Iron, phosphorus, sulfur, and silicon interact strongly with As during its route from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
642
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,071 publications
(658 citation statements)
references
References 151 publications
11
642
0
5
Order By: Relevance
“…The rice rhizosphere is the crucial microenvironment influencing As bioavailability and uptake into rice plants. 46 The rice rhizosphere was different in soil physical− chemical properties, shown by the elevated Eh and the lower soil pH ( Figures S5 and S6, Supporting Information). Arsenicoxidizing microbes were usually aerobic and thus were more likely to be elevated in the rice rhizosphere.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The rice rhizosphere is the crucial microenvironment influencing As bioavailability and uptake into rice plants. 46 The rice rhizosphere was different in soil physical− chemical properties, shown by the elevated Eh and the lower soil pH ( Figures S5 and S6, Supporting Information). Arsenicoxidizing microbes were usually aerobic and thus were more likely to be elevated in the rice rhizosphere.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The only increase in shoot As concentration in BBC indicated the influenced translocation of As in plant by biochar amendment in keeping with our previous study . However, the pathway of As translocation in rice plant involving As sequestration in vacuoles, loading and unloading in xylem and phloem, and reduction or methylation responsible by enzymes remains poorly understood (Zhao et al 2010). Much further research needs to be undertaken to unravel the mechanisms influencing As translocation in plants.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Arsenic exposure from water and diet has now become a global health issue (Berg et 1,6,7 Furthermore, among cereal crops, rice is much more efficient at accumulating As due to its requirement for waterlogged conditions which enhance As mobility (Su et 11,16,17 The As species present in soils and rice plants are mainly inorganic As [arsenite (AsIII) and arsenate (AsV)] and organic As [monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA)], with inorganic As being the predominant species Zheng et al, 2013;Wu et al, 2015). 2,18,19 Studies have demonstrated that oxic conditions in soils play an important role in As uptake and speciation in rice plants (Xu et al, 2008;Somenahally et al, 2011). 9,20,21 In aerobic conditions, Arsenate [As(V)] predominates, with low bioavailability, due to it being strongly adsorbed by Fe and Al (hydr)oxides (Xu et 18,20,21,23 thereby making As(III) the predominant As species in flooded paddy soils.…”
Section: Introductionmentioning
confidence: 99%
“…2,18,19 Studies have demonstrated that oxic conditions in soils play an important role in As uptake and speciation in rice plants (Xu et al, 2008;Somenahally et al, 2011). 9,20,21 In aerobic conditions, Arsenate [As(V)] predominates, with low bioavailability, due to it being strongly adsorbed by Fe and Al (hydr)oxides (Xu et 18,20,21,23 thereby making As(III) the predominant As species in flooded paddy soils. Xu et al 20 (2008) and Li et al 21 (2009) observed that growing rice aerobically significantly reduced total As concentrations in the soil solution, whilst also markedly reducing total As and iAs concentrations in rice grain compared to those grown in flooded conditions.…”
Section: Introductionmentioning
confidence: 99%